Sexual orientation and wage discrimination: evidence from Australia. Issue 6 (25th July 2019) - Preston, Alison; Birch, Elisa; Timming, Andrew R.
Abstract : Purpose: The purpose of this paper is to document the wage effects associated with sexual orientation and to examine whether the wage gap has improved following recent institutional changes which favour sexual minorities. Design/methodology/approach: Ordinary least squares and quantile regressions are estimated using Australian data for 2010–2012 and 2015–2017, with the analysis disaggregated by sector of employment. Blinder–Oaxaca decompositions are used to quantify unexplained wage gaps. Findings: Relative to heterosexual men, in 2015–2017 gay men in the public and private sectors had wages which were equivalent to heterosexual men at all points in the wage distribution. In the private sector: highly skilled lesbians experienced a wage penalty of 13 per cent; low-skilled bisexual women faced a penalty of 11 per cent, as did bisexual men at the median (8 per cent penalty). In the public sector low-skilled lesbians and low-skilled bisexual women significant experienced wage premiums. Between 2010–2012 and 2015–2017 the pay position of highly skilled gay men has significantly improved with the convergence driven by favourable wage (rather than composition) effects. Practical implications: The results provide important benchmarks against which the treatment of sexual minorities may be monitored. Originality/value: The analysis of the sexual minority wage gaps by sector and position on the wage distribution and insight into the effect of institutions on the wages of sexual minorities.